Influence of the Maternal Use of Labetalol on the Neurogenic Mechanism for Cerebral Autoregulation Assessed by Means of NIRS (2014)
Labetalol is a drug used in the treatment of hypertensive disorders of pregnancy (HDP). In a previous study we investigated the influence of the maternal use of labetalol on the cerebral autoregulation (CA) mechanism of neonates. In that study, we found that labetalol induces impaired CA during the first day of life, with CA returning to a normal status by the third day after birth. This effect was hypothesized to be caused by labetalol-induced vasodilation. However, no strong evidence for this claim was found. In this study we aim to find stronger evidence for the vasodilation effect caused by labetalol, by investigating its effect on the neurogenic mechanism (NM) involved in CA. The status of the NM was assessed by means of transfer function analysis between the low frequency content of the autonomic control activity (LFA), obtained by processing of the heart rate (HR), and the regional cerebral oxygen saturation (rScO2). We found that neonates from mothers treated with labetalol presented a lower LFA and an impaired NM response during the first day of life, with values returning to normal by the end of the third day. These results reflect a vasodilation effect caused by labetalol, and indicate that the impaired CA observed in the previous study is caused by vasodilation.